Entrepreneurial teams and new business creation - Vanaelst, Iris; Wright, Mike , 1952- (An Elgar reference collection, 2009)
Curiosity is focused on how entrepreneurial teams should be formed in order to allow new businesses to be created and to ensure their growth. This title identifies leading contributions to this area and reflects a growing body of research.